Educação para além do capital e políticas educacionais na América Latina - Novaes, Henrique Tahan (Editora Oficina Universitária, 2022)
The collection "Education beyond capital and educational policies in Latin America", organized by Henrique Tahan Novaes, brings together a set of thirteen chapters with texts resulting from research that analyze educational policies in Latin America as well as the resistance and construction of alternatives education by some of its social movements. In the context of Latin America, Chapter 2, by Henrique Tahan Novaes and Julio Hideyshi Okumura, discusses "The role of Foundations, NGOs and institutes in the destruction of public education in Latin America". Two chapters bring reflections on education in Argentina: Chapter 1 - Educational policies in Argentina: the right to education in dispute - by Esther Levy; and Chapter 12 -The Facultad Abierta Program, of decades with recovered and self-managed companies - by Andres Ruggeri. Different reflections on education in Brazil, notably on the construction by the MST of educational alternatives, are in five chapters: Chapter 5, written by Messilene Gorete da Silva and Rosana Cebalho Fernandes, deals with The Florestan Fernandes National School and its organization formative; Chapter 6 - presents an exposition on "Political formation in the MST: reflections on the repercussions of the water crisis in the struggle for land", written by Marília Fonseca Del Passo and Fabiana de Cássia Rodrigues; in Chapter 7, by Henrique Tahan Novaes and João Henrique Pires, the "Contributions of the MST Agroecology Schools for the formation of an educational system beyond capital" are analyzed; in Chapter 8, the "Movement of Landless Rural Workers (MST): educational background, gender and pandemic", by Neusa Maria Dal Ri; Chapter 11 brings "An assessment of the performance of Cooperative Incubators in Brazil", by Felipe Addor. Reflections on the survival of public education in Chile can be found in Chapter 3, "Educación en Chile: Pensar lo Público en el 'oasis' neoliberal", by Rodrigo Sánchez, Edmonson and Erick Valenzuela Bello. Chapter 10 is entitled "Class struggle and popular education in El Salvador: peasant communities and their historical legacy of self-organization", written by María Gabriela Guillén Carías. In Chapter 4, an analysis is made of the "Intervención educacao y trabajo comunitario en México", by Ana Alicia Peña López and Nashelly Ocampo Figueroa. On Uruguay, Chapter 9 focuses on "Escuela de formación de la FUCVAM: unaexperience de formación uruguayan", written by Juan Zerboni. The collection closes with chapter 13, bringing a text with a set of four reflections by Renato Dagnino on Science, Technology and Society; Solidary Technoscience; on "Bem Viver" and on the curriculum of university extension in Brazil.